EVALUATION OF SERUM SIALIC ACID LEVELS IN HEAD AND NECK MALIGNANCIES - RATHAN SHETTY K. S; ARUNAVA KALI (International Journal of Pharma and Bio Sciences, 2014)
Head and neck cancers (HNC) have emerged as a leading cause of cancer related mortality and morbidity worldwide. Especially in developing countries, due to a lack of awareness and healthcare facilities, most HNC cases are diagnosed at advanced stages. Currently, there are no reliable non-invasive diagnostic modalities to detect HNC and follow up treated cases. Serum sialic acid is a promising cancer biomarker which could be crucial in HNC diagnosis. The aim of this study was to analyse pre and post-operative levels of serum sialic acid in HNC patients in comparison with healthy controls. We have estimated the pre- and post-operative serum sialic acid levels in 65 patients with histopathologically confirmed HNC who underwent surgery and compared them with those of 65 healthy controls. Compared to the control group, HNC patients had statistically significant elevation in serum sialic acid levels over normal mean value. The post-operative serum sialic acid levels showed statistically significant reduction and correlated well with postoperative events. Serum sialic acid is a non-invasive and costeffective technique which may be employed as an adjunct to histopathology for early detection and monitoring of HNC patients.